Collisions of Rydberg atoms with neutral targets. Issue 2 (3rd April 2018) - Dunning, F. B.; Buathong, S.
ABSTRACT: Atoms in highly excited Rydberg states possess physical characteristics quite unlike those associated with atoms in the ground or low-lying excited states. In particular, they are physically very large and are only very weakly bound. In consequence, collisions can lead to a wide variety of reaction processes many of which are unique to Rydberg species and have very large collision cross sections. In collisions with neutral targets, Rydberg atoms behave not as an atom but rather as a pair of well-separated independent scatterers, namely the core ion and the excited Rydberg electron. In the present article we discuss many of the different reactions that can occur when Rydberg atoms collide with neutral targets, focusing principally on reactions that are dominated by (binary) Rydberg electron-target interactions and include collisions with molecules that attach free low-energy electrons and with polar targets. In certain situations, however, interactions involving the Rydberg core ion are important. This is illustrated using as an example the destruction of ultralong-range Rydberg molecules excited in a cold dense gas.